Complete mitochondrial genome of the H3 haplotype Argentine ant Linepithema humile (Mayr, 1868) (Formicidae; Hymenoptera). Issue 3 (4th March 2021) - Park, Jonghyun; Park, Chan-Ho; Park, Jongsun
Abstract: The argentine ant, Linepithema humile (Mayr, 1867), is an invasive ant species that has spread across the world. We have determined the mitochondrial genome of L. humile collected in South Korea, which is 15, 934 bp containing 10 SNPs and 5 INDELs compared to the previous mitogenome. Most SNPs were found in cox3, followed by cytb . From SNPs our mitogenome was identified as a H3 haplotype, which was previously recorded in Japan and the U.S. while the previous mitogenome was H1 haplotype. Phylogenetic analysis was congruent to previous study within the tribe Leptomyrmecini but not between other tribes of subfamily Dolichoderinae.